2014
DOI: 10.1007/s10096-014-2162-3
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiome analysis as a diagnostic test for diverticulitis

Abstract: Disease-specific variations in intestinal microbiome composition have been found for a number of intestinal disorders, but little is known about diverticulitis. The purpose of this study was to compare the fecal microbiota of diverticulitis patients with control subjects from a general gastroenterological practice and to investigate the feasibility of predictive diagnostics based on complex microbiota data. Thirty-one patients with computed tomography (CT)-proven left-sided uncomplicated acute diverticulitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 42 publications
1
110
1
3
Order By: Relevance
“…RF, NSC, ENET, SVM, and PLS-DA have all been successfully applied in human microbiota classification tasks (22,26), as well as in genomics, a field with similar dimensionality challenges (31)(32)(33)(34)(35). We used the following publicly available packages in the statistical software R: randomForest with default settings for the RF classifier; LiblineaR with type "L1-regularized L2-loss support vector classification" and the cost constant tuned by the heuristics provided by the heuristicC function for SVM; glmnet with ␣ values of 0, 1, and 0.5 for L2-and L1-regularized logistic regression and ENET, respectively; caret for PLS-DA; and pamr for the NSC classifier.…”
Section: Methodsmentioning
confidence: 99%
“…RF, NSC, ENET, SVM, and PLS-DA have all been successfully applied in human microbiota classification tasks (22,26), as well as in genomics, a field with similar dimensionality challenges (31)(32)(33)(34)(35). We used the following publicly available packages in the statistical software R: randomForest with default settings for the RF classifier; LiblineaR with type "L1-regularized L2-loss support vector classification" and the cost constant tuned by the heuristics provided by the heuristicC function for SVM; glmnet with ␣ values of 0, 1, and 0.5 for L2-and L1-regularized logistic regression and ENET, respectively; caret for PLS-DA; and pamr for the NSC classifier.…”
Section: Methodsmentioning
confidence: 99%
“…Los resultados demostraron que la relación Firmicutes/Bacteroidetes y la carga de proteobacterias eran comparables. Sin embargo, una mayor diversidad de proteobacterias y de todos los phyla fue encontrada en pacientes con diverticulitis 34 . Estudios deberán definir el papel de la microbiota en la ED.…”
Section: Microbiotaunclassified
“…Using a polymerase chain reaction-based profiling technique on DNA isolates from fecal samples, Daniels et al [22] recently compared the fecal microbiota of diverticulitis patients with control subjects from a general gastroenterological practice. They found that Firmicutes/Bacteroidetes ratios and Proteobacteria load were comparable among patients and controls (p = 0.20), while a higher diversity in diverticulitis for Proteobacteria (p < 0.00002) and all phyla combined (p = 0.002) were found.…”
Section: Microbiota Alterationsmentioning
confidence: 99%